2022
DOI: 10.1109/ojcsys.2022.3178540
|View full text |Cite
|
Sign up to set email alerts
|

Non-Stationary Representation Learning in Sequential Linear Bandits

Abstract: In this paper, we study representation learning for multi-task decision-making in non-stationary environments. We consider the framework of sequential linear bandits, where the agent performs a series of tasks drawn from different environments. The embeddings of tasks in each environment share a lowdimensional feature extractor called representation, and representations are different across environments. We propose an online algorithm that facilitates efficient decision-making by learning and transferring nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, a key distinction is that, in ICL, adaptation to a new task happens implicitly through input prompt. Our analysis has some parallels with recent literature on multitask representation learning [32,13,51,8,26,21,42,50,10,34,14,58] since we develop excess MTL risk bounds by training the model with 𝑇 tasks and quantify these bounds in terms of complexity of the hypothesis space (i.e. transformer architecture), the number of tasks 𝑇, and the number of samples per task.…”
Section: F Further Related Work On Multitask/meta Learningmentioning
confidence: 85%
See 1 more Smart Citation
“…However, a key distinction is that, in ICL, adaptation to a new task happens implicitly through input prompt. Our analysis has some parallels with recent literature on multitask representation learning [32,13,51,8,26,21,42,50,10,34,14,58] since we develop excess MTL risk bounds by training the model with 𝑇 tasks and quantify these bounds in terms of complexity of the hypothesis space (i.e. transformer architecture), the number of tasks 𝑇, and the number of samples per task.…”
Section: F Further Related Work On Multitask/meta Learningmentioning
confidence: 85%
“…Here the first term in (42) comes from the fact that loss function is bounded by 𝐵, and we assume S (0) = ∅, and the second term follows the Hypothesis 1. Next, we turn to bound risk(ℎ, 𝑚).…”
Section: E Model Selection and Approximation Error Analysismentioning
confidence: 99%
“…Cella et al (2022a,b) also investigate the problem in Yang et al (2021) and propose algorithms which do not need to know the dimension of the underlying representation. Qin et al (2022) study representation learning for linear bandit under non-stationary environments, and develop algorithms that learn and transfer non-stationary representations adaptively. Different from the above works which consider regret minimization, we study representation learning for (contextual) linear bandit with the pure exploration objective, which imposes unique challenges in how to optimally allocate samples to learn the feature extractor, and motivates us to design algorithms building upon double experimental designs.…”
Section: Appendix a Related Workmentioning
confidence: 99%
“…Multitask bandits, multitask RL and meta-RL: The benefit of multitask learning in linear bandits has been investigated in Yang et al (2021); Qin et al (2022); Cella et al (2022); Azizi et al (2022); Deshmukh et al (2017); Cella and Pontil (2021); Hu et al (2021). For multitask RL, Arora et al (2020) showed that representation learning can reduce sample complexity for imitation learning.…”
Section: Related Workmentioning
confidence: 99%
“…In downstream, with the help of the learned representation, the agent aims to find a near-optimal policy of a new task that shares the same representation as the source tasks. While representation learning has achieved great success in supervised learning (Du et al, 2020;Tripuraneni et al, 2021;Maurer et al, 2016;Kong et al, 2020) and multi-armed bandits (MAB) problems (Yang et al, 2021;Qin et al, 2022;Cella et al, 2022), most works in multitask RL mainly focus on empirical algorithms (Sodhani et al, 2021;Arulkumaran et al, 2022;Teh et al, 2017) with limited theoretical works (Arora et al, 2020;Hu et al, 2021;Brunskill and Li, 2013;Müller and Pacchiano, 2022;Calandriello et al, 2015;Lu et al, 2021;D'Eramo et al, 2020). Generally speaking, there are two main challenges for multitask representation learning in RL.…”
Section: Introductionmentioning
confidence: 99%